Factors Responsible for the Students Declining Interest in Primary Education in Anambra State, Nigeria - Ifeoma Chinyere Umeji (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Student interest in pursuing primary education has been declining in Anambra State, Nigeria, raising concerns about the future of foundational education and its role in national development. Understanding the root causes of this trend is essential for implementing effective interventions. Objective: This study aimed to explore the factors responsible for the waning enthusiasm for primary education among students in Anambra State and to propose strategies to address this issue. Method: A survey research design was adopted, targeting students enrolled in primary and early childhood education programs across tertiary institutions in Anambra State. Data were collected using a self-structured questionnaire administered via Google Forms. The instrument was validated by experts and tested for reliability. Responses from 100 participants were analyzed using SPSS, employing weighted mean scores to determine the perceived influence of various factors. Result: The analysis revealed that several interconnected factors contributed to the declining interest in primary education. These included poor educational infrastructure, insufficient funding, low levels of motivation among students and teachers, negative societal perceptions, and a shortage of qualified teaching staff. Conclusion: The findings indicate an urgent need for comprehensive reforms in primary education. Addressing these challenges through targeted investment, motivation initiatives, public perception campaigns, and strategic recruitment efforts is essential to revitalize student interest and strengthen the primary education system. Contribution: This study contributes to educational research by offering empirical insights into the specific challenges affecting primary education in Anambra State. It also provides practical recommendations for policymakers and education stakeholders aimed at improving student enrollment and interest in the field.